Discovery, Structure-Activity Relationship and Biological Activity of Histone-Competitive Inhibitors of Histone Acetyltransferases P300/CBP - Wu, Fangrui (J Med Chem, 2020)
Histone acetyltransferase (HAT) p300 and its paralog CBP acetylate histone lysine sidechains and play critical roles in regulating gene transcription. The HAT domain of p300/CBP is a potential drug target for cancer. Through compound screening and medicinal chemistry, novel inhibitors of p300/CBP HAT with their IC(50)s as low as 620 nM were discovered. The most potent inhibitor is competitive against histone substrates and exhibits a high selectivity for p300/CBP. It inhibited cellular acetylation and had strong activity with EC(50) of 1-3 μM against proliferation of several tumor cell lines. Gene expression profiling in estrogen receptor (ER)-positive breast cancer MCF-7 cells showed that inhibitor treatment recapitulated siRNA-mediated p300 knockdown, inhibited ER-mediated gene transcription, and suppressed expression of numerous cancer-related gene signatures. These results demonstrate that the inhibitor is not only a useful probe for biological studies of p300/CBP HAT, but also a pharmacological lead for further drug development targeting cancer.